2021
DOI: 10.3390/molecules26041091
|View full text |Cite
|
Sign up to set email alerts
|

Optical Response Characteristics of Single-Walled Carbon Nanotube Chirality Exposed to Oxidants with Different Oxidizing Power

Abstract: Semiconductor single-walled carbon nanotubes (SWNTs) have unique characteristics owing to differences in the three-dimensional structure (chirality) expressed by the chiral index (n,m), and many studies on the redox characteristics of chirality have been reported. In this study, we investigated the relationship between the chirality of SWNTs and the oxidizing power of oxidants by measuring the near-infrared (NIR) absorption spectra of two double-stranded DNA-SWNT complexes with the addition of three oxidants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…As shown in Figure 10 , the adenine- and cytosine-wrapped SWCNTs exhibit significant spectral changes beyond 570 nm compared to bare SWCNTs. This result can be expected to support the explanation of the cause of the absorption spectra change of DNA–SWCNTs shown in the previous research [ 11 ]. The experimental results of the light absorption spectra obscure the intrinsic properties of the structure of DNA–SWCNTs due to the composite effects of solvents.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…As shown in Figure 10 , the adenine- and cytosine-wrapped SWCNTs exhibit significant spectral changes beyond 570 nm compared to bare SWCNTs. This result can be expected to support the explanation of the cause of the absorption spectra change of DNA–SWCNTs shown in the previous research [ 11 ]. The experimental results of the light absorption spectra obscure the intrinsic properties of the structure of DNA–SWCNTs due to the composite effects of solvents.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are expected to accelerate the study of optical characteristics of base-wrapped DNA–SWCNTs. Furthermore, the previous experimental study showed that the peak of the molar absorbance coefficient was observed near 990 nm [ 11 ]. In the previous study, redox reactions were known to change the light absorption spectra, but the cause had not been identified experimentally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation